Adoption Level of Soil and Water Conservation Technology under NICRA in Chatra District in Jharkhand - Oraon, D.; Kumar, Anjani h4; Singh, R K; Singh, U K (Indian Journal of Extension Education, 2020)
Many states in India are affected by land and water degradation. Successive technologies have been promoted to prevent soil and water conservation on a large scale. This paper deals adoption level of soil and water conservation technologies in purposively selected NICRA village of Chatra district in Jharkhand, India. A total of 105 farm families were selected purposively for the study. Data collected through personal interviews, group meetings, and structured schedule from selected respondents. It was found that under crop production (SWC), Soil and water conservation technology, intercropping (88.57%), whereas under mechanical SWC technologies, land leveling (97.14%) was adopted by farmers. Most of the respondents come under a medium level of adopter categories related to soil and water conservation technologies.